Everything you need to know now about gold and silver - Carabini, Louis E. (New Rochelle, N.Y., Arlington House, 1974)
The book examines the importance of gold and silver in trade and production of goods and services. It also considers other economic issues like inflation, price controls, shortages, balance of payments deficits etc.
Reprints of interviews from the Gold & silver newsletter.
Bibliography: p. 159-176.
usc 7/11/18
Loans
Keywords: Precious metals; Gold; Silver